PENGARUH SIKAP KEWIRAUSAHAAN DAN PROSES INOVASI TERHADAP KEBERHASILAN USAHA PADA RUMAH BATIK KOMAR DI KOTA BANDUNG - Handayani, Trustorini; Tanjung, Yusuf (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2017)
The purpose of this study is to find out and analyze the influence of Entrepreneurial attitude and Innovation Process of business succes at Rumah Batik Komar. The result of the study shows that the business succes in this company is still on low level. It is understandable considering that the owner is so uneasy in taking any risk, the raw material for this industry is very expensive, and there is no participation from the government. The methods in this study are descriptive analysis, verification analysis and multiple linear regressions. The result of the study shows that there are some significant connection between Entrepreneurial attitude and the innovation of business success at the Rumah Batik Komar . The technique of determining the data used are the judgmental methods as much as 27 employee. To know the influence of entrepreneurial attitude perceptions and Innovation Process of business succes of p used Statistics analysis i.e. using multiple linear regression analysis, correlation coefficient, coefficient of determination, and test the hypothesis with trials F and t-test, using the help application programs 20 SPSS for windows. The Results of study showed there was perception influence consumer Entrepreneurial attitude and Innovation Process Rumah Batik Komar. Based on the results of partial test can be seen that Entrepreneurial attitude and Innovation Process of in a positive and significant effect business success Summary of the research is the higher the perception of Entrepreneurial attitude and Innovation Process of business success will be increasing. Keywords: Entrepreneurial attitude, Innovation Process, success of the business